2020
DOI: 10.3390/agronomy10050656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity and Nitrogen Sources on the Leaf Quality, Biomass, and Metabolic Responses of Two Ecotypes of Portulaca oleracea

Abstract: Halophytic plants are, by definition, well adapted to saline soils. However, even halophytes can face nutritional imbalance and the accumulation of high levels of compounds such as oxalic acid (OA), and nitrate (NO3−). These compounds compromise the potential nutritional health benefits associated with salt-tolerant plants such as Portulaca oleracea or Purslane. Purslane has long been known to be a highly nutritious leafy vegetable particularly with respect to high levels of omega-3 fatty acids. Thus, preventi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…POR-2936) exposed to 100 mM NaCl presented higher shoot and root productivity, as compared to those grown with 0 mM NaCl [5]. However, the growth of an Aegean purslane accession was more suppressed under 140 mM NaCl than 70 mM NaCl [32], suggesting that the salinity concentration threshold to affect growth differs for each genotype [33]. Thus, increases in fresh weight rising salinity have been recorded in some purslane accessions (e.g., in Ac9), even up to 32 dS m −1 [12].…”
Section: Yieldmentioning
confidence: 93%
See 3 more Smart Citations
“…POR-2936) exposed to 100 mM NaCl presented higher shoot and root productivity, as compared to those grown with 0 mM NaCl [5]. However, the growth of an Aegean purslane accession was more suppressed under 140 mM NaCl than 70 mM NaCl [32], suggesting that the salinity concentration threshold to affect growth differs for each genotype [33]. Thus, increases in fresh weight rising salinity have been recorded in some purslane accessions (e.g., in Ac9), even up to 32 dS m −1 [12].…”
Section: Yieldmentioning
confidence: 93%
“…Although the unsaturated fatty acids have emerged as general protectors against different abiotic and biotic stress [78], in our study, this effect was not observed, probably due to the salinity tolerance of purslane microgreens. However, Camalle et al [33] observed differences with respect to total fatty acid content for the purslane ecotypes and nitrate to ammonium ratio tested, with an increase under saline conditions for ecotype ET compared to ecotype RN. In addition, changes in the fatty acid composition of leaves were detected and fatty acid contents were affected by salinity in borage, with LNA content being the most affected [79].…”
Section: Fatty Acidsmentioning
confidence: 94%
See 2 more Smart Citations
“…Purslane has long been known to be a highly nutritious leafy vegetable particularly with respect to high levels of omega-3 fatty acids. Thus, preventing the accumulation of non-nutritional compounds will allow plants to be grown in saline conditions as crops [1]. Purslane (Portulaca oleracea L.) is the eighth most common plant distributed throughout the world, because it is an important heat-and drought-tolerant vegetable crop [2].…”
Section: Introductionmentioning
confidence: 99%